PENGARUH REGULASI PEMERINTAH, TEKANAN MASYARAKAT, TEKANAN ORGANISASI LINGKUNGAN, TEKANAN MEDIA MASSA, TERHADAP CORPORATE SOCIAL DISCLOSURE - Basuki Basuki; Corry Natasha Patrioty (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
In recent conditions, company is not considers merely on profit, but there is strong argument that company must aware on its social environments. Hence, it is required that a company must disclose its social responsibility to the stakeholders. Corporate social disclosure itself is influenced by many factors. The objective of this study is to explain the influencing factors of corporate social responsibility. Based on the Stakeholders theory, the study will investigated social responsibility accounting phenomena on business practices. The research sites would be in PTPN- East Java consists of PTPN X, XI, and XII. Regressions models are used to test the formulated hypothesis. Data were collected by using questionnaires which were mailed to 58 top and middle managers in PTPN who directly or indirectly involved in the corporate social responsibility. The empirical finding showed that and partially Mass media pressure are significant factor to corporate social disclosure, meanwhile Government regulation, Community pressure, environmental organization pressure do not have significant effect on corporate social disclosure. However, simultaneously those factors significantly influence the PTPTN’s corporate social disclosure.